Evaluasi Pelaksanaan Program System Coaching Clinic (SCOCI) di Balai Diklat Keagamaan Denpasar - Agustini, Ni Made Sri; Suyatno (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2023)
Innovation in the training field is developed to accommodate employee rights in the work area. One form of competency development that can be implemented to achieve flexible targets with maximum product output is the System Coaching Clinic (SCOCI). This research aims to measure the extent to which SCOCI helps resolve service performance problems at the Denpasar Religious Education and Training Center and analyze gaps in implementation with existing guidelines and regulations. The research method used in this study is the evaluation method with the discrepancy model. This study evaluates how SCOCI helps solve service performance problems at Denpasar Religious Education and Training Center and determines implementation gaps with existing guidelines and regulations. The SCOCI program is beneficial in increasing competence because of the intense mentoring and the small number of participants; the SCOCI Program brings harmony to work culture management and builds work networks and collaborations. SCOCI program helps improve organizational performance related to increasing the professionalism of ASNs by fulfilling 20 JP training services a year, which cannot be accommodated in PDWK, PJJ, or regular training. SCOCI as a training development activity can be implemented more flexibly by prioritizing service to participants so that participants will feel comfortable being motivated while producing useful and quality training products. The SCOCI program can be continued as a priority program for the Denpasar Religious Training Center, but a simplified registration and selection process needs to be done.(Inovasi dalam bidang pelatihan merupakan sesuatu yang dikembangkan untuk mengakomodir hak pegawai di wilayah kerja. Salah satu bentuk pengembangan kompetensi yang dapat dilaksanakan untuk mencapai target, bersifat fleksibel dengan hasil output produk yang maksimal adalah System Coaching Clinic (SCOCI). Penelitian ini bertujuan untuk mengukur sejauh mana SCOCI bermanfaat dalam menyelesaikan permasalahan kinerja layanan Balai Diklat Keagamaan denpasar dan menganalisis kesenjangan implementasi dengan panduan dan regulasi yang ada. Metode penelitian yang digunakan dalam penelitian ini adalah metode evaluasi dengan model discrepancy. Penelitian ini mengevaluasi sejauhmana SCOCI bermanfaat dalam menyelesaikan permasalahan kinerja layanan Balai Diklat Keagamaan denpasar dan mengetahui kesenjangan implementasi dengan panduan dan regulasi yang ada. Program SCOCI sangat bermanfaat dalam meningkatkan kompetensi karena pembimbingan intens dan jumlah peserta dengan skala kecil, Program SCOCI membawa pengelolaan budaya kerja yang harmoni serta Membangun Jejaring Kerja dan Kolaborasi. program SCOCI membantu peningkatan kinerja organisasi terkait peningkatan profesionalisme terhadap ASN dengan terpenuhinya pelayanan pelatihan 20 JP setahun yang tidak dapat terakomodir dalam pelatihan PDWK, PJJ, maupun pelatihan reguler. SCOCI sebagai kegiatan pengembangan pelatihan dapat dilaksanakan lebih fleksible dengan mengutamakan pelayanan kepada peserta sehingga peserta akan merasa nyaman termotivasi sekaligus menghasilkan hasil produk pelatihan yang useful dan berkualitas. Program SCOCI dapat dilanjutkan sebagai program prioritas Balai Diklat Keagamaan Denpasar namun perlu ada proses registrasi dan seleksi yang lebih simple dan sederhana.)